Phase Ia/Ib Study of the Selective MET Inhibitor, Savolitinib, in Patients with Advanced Solid Tumors: Safety, Efficacy, and Biomarkers. (21st April 2022) - Wang, Yakun; Liu, Tianshu; Chen, Gongyan; Gong, Jifang; Bai, Yuxian; Zhang, Tao; Xu, Nong; Liu, Li; Xu, Jianming; He, Jianxing; Liu, Yunpeng; Zhang, Li; et al.
Abstract : Savolitinib is a novel reversible and competitive c-Met kinase inhibitor that has shown antitumor activity. The aim of this study was to confirm in Chinese patients the recommended phase II dose of savolitinib and to explore overall benefit in tumors bearing c-Met aberration. Abstract: Background: Savolitinib has shown good tolerability and preliminary efficacy, but efficacy biomarkers require investigation. The main purpose of this study was to confirm in Chinese patients the recommended phase II dose (RP2D) of savolitinib and to explore overall benefit in tumors bearing c-Met aberration. Methods: This was an open-label, multi-center, 2-part phase I study. A starting dose of 600 mg QD was initiated in the escalation phase, utilizing a 3+3 design with repeated QD and BID dosing. In the dose expansion phase, we enrolled patients with gastric cancer and non–small cell lung cancer (NSCLC) with documented c-met aberration into 5 cohorts to further explore biomarkers. c-Met overexpression and amplification were assessed by immunohistochemistry and FISH, respectively. Results: The safety analysis set included 85 patients. Only one dose-limiting toxicity (grade 3 fatigue) was reported in the 600 mg BID dosing group. The most frequent treatment-related adverse events were nausea (29.4%), vomiting (27.1%), and peripheral edema (21.2%). Notably, in gastric cancer, response was only observed in patients with MET amplification (copy number 9.7-18.4), with an objective response rate of 35.7% and a disease control rate of 64.3%. For patients with NSCLC bearing a MET exon 14 skipping mutation, obvious target lesion shrinkage was observed in 2 of 4 patients, although PR was not achieved. Conclusion: The RP2D of savolitinib was established as 600 mg QD or 500 mg BID in Chinese patients. The promising response observed in patients with gastric cancer with c-met amplification and NSCLC with MET exon 14 skipping mutation warrants further investigation. ClinicalTrials.gov Identifier: NCT0198555